Aporia [videorecording (Blu-Ray)] - Moshé, Jared; Greer, Judy, 1975-; Gathegi, Edi; Muʻādī, Paymān, 1972-; Herman, Faithe, 2007- (Well Go USA, 2023)
Since losing her husband in a drunk-driving accident, Sophie has struggled to manage crippling grief, a full-time job, and the demands of parenting her devastated teen daughter. When her husband's best friend, a former physicist, reveals that he has been building a time-bending machine that could restore her former life, she is faced with an impossible choice. One push of a button and she can kill the drunk driver and bring her husband back but changing the past to save a loved one has unforeseeable consequences.